Physiological Antioxidative Network of the Bilirubin System in Aging and Age-Related Diseases - Kim, Sung Young; Park, Sang Chul (Frontiers in Pharmacology, 2012)
Oxidative stress is detrimental to life processes and is particularly responsible for aging and age-related diseases. Thus, most organisms are well equipped with a spectrum of biological defense mechanisms against oxidative stress. The major efficient antioxidative mechanism is the glutathione system, operating a redox cycling mechanism for glutathione utilization, which consists of glutathione and its peroxidase and reductase. However, this system is mainly effective for hydrophilic oxidants, while lipophilic oxidants require another scavenging system. Since many age-related pathological conditions are related to lipid peroxidation, especially in association with the aging process, the physiological role of the scavenging system for lipophilic oxidants should be considered. In this regard, the biliverdin to bilirubin conversion pathway, via biliverdin reductase, is suggested to be another major protective mechanism that scavenges lipophilic oxidants because of the lipophilic nature of bilirubin. The efficiency of this bilirubin system might be potentiated by operation of the intertwined bicyclic systems of the suggested redox metabolic cycle of biliverdin and bilirubin and the transcriptional control cycle of biliverdin reductase and heme oxygenase-1. In order to combat oxidative stress, both anti-oxidative systems, against hydrophilic and lipophilic oxidants, respectively, are required to work cooperatively. In this regard, the roles of the bilirubin system in aging and age-related diseases are reassessed in this review, and their interacting networks are evaluated.